FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK, DENGAN PENDEKATAN PERILAKU DAN ETIKA (Studi Empiris Pada Perusahaan PMA Yang Terdaftar Di Kanwil DJP Jakarta Khusus) - Deden Tarmidi; Waluyo Waluyo (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2014)
The purpose of this research is examine the factors that affect tax compliance, with the approach  Theory of Planned Behavior (TPB) and ethics. The fact that tax compliance is still low in Indonesia, including foreign investment companies (PMA). Variables used for this research based on some previous research such as Schifter and Ajzen (1985), Ajzen (1991), Recker (1994), Hanno and Violette (1996), Blanthorne (2000), Bobek and Hatfield (2003) Ajzen and Fishbein (2005), Trivedi et. al. (2005), Mustikasari (2007), Hutagaol (2007), Harinurdin (2009), Wangsa (2009), Ernawati and Purnomosidhi (2011), and Damayanti (2012) with slight modification. The samples of this research consisted of one hundred and fifty tax professional as a representative of  foreign investment company (PMA) in Kanwil DJP Jakarta Khusus. Structural Equation Modeling (SEM) was used for data analysis. The result showed that ethics of tax professional as PMA representative contributes a significant positive to tax compliance. The empirical results show that in order to improve tax compliance behavior of taxpayers, ethics in environment must continue to growed, Directorate General of Taxation can conduct a psychological approach to the taxpayer in order to further improve compliance in implementing their taxation . Keywords: Theory of Planned Behavior, Ethics, Tax Compliance